Progressive Failure of Surrounding Rock in Underground Engineering and Size Effect of Numerical Simulation - Daning Zhong; Jianlin Chen; Hui Zhou; Xiangrong Chen; Yali Jiang (Advances in Civil Engineering)
The analysis and simulation of progressive failure of surrounding rock is very important for analyzing the stability of surrounding rock in underground engineering. Size effect is also a key problem worth further study in engineering. Taking the underground powerhouse on the right bank of Baihetan as an example, the acoustic test results are collected and the relaxation and failure characteristics of the surrounding rock are summarized. Then, the numerical simulation of progressive failure of surrounding rock of underground powerhouse is carried out by using the finite discrete element method CDEM (continuum-based discrete element method). The results are compared with the acoustic test results of the surrounding rock relaxation layer, and the stress and displacement of surrounding rock characteristic points are analyzed. At the same time, the size effect of grid and mechanical parameter in the process of numerical simulation are discussed. The calculated fracture depth of surrounding rock is in good agreement with the acoustic test results, which shows the reliability of progressive failure simulation of surrounding rock of the underground powerhouse. When CDEM is used to simulate the excavation of tunnels with different tunnel diameters, the minimum grid size should be about 1% of the tunnel diameter. The mechanical parameters of rock mass have significant size effect, which needs to be analyzed in detail. The research results prove the superiority of the CDEM method in simulating the progressive failure of hard surrounding rock and its unique size effect characteristics, which can provide technical reference for the application of the CDEM method in other similar engineering problems.